FRI0464 Long-Term Efficacy of Ustekinumab Treatment in Patients Affected by Psoriatic Arthritis Previously Treated with TNF Inhibitors. (15th July 2016) - Chimenti, M.S.; Triggianese, P.; Ortolan, A.; Tonelli, M.; Talamonti, M.; Costa, L.; Caso, F.; Teoli, M.; Galluzzo, M.; Ramonda, R.; Scarpa, R.; Punzi, L.; et al.
Abstract : Background: IL12 and IL23 are two main cytokines involved in the pathogenesis of immune-mediated diseases. IL-12 is produced by macrophages and B lymphocytes and mediates differentiation of Th1 lymphocytes, while IL-23 is a pro-inflammatory cytokine essential for the differentiation of Th17 cells. Ustekinumab is a human monoclonal antibody directed against the p40 protein subunit shared by IL-12 and IL-23, blocking the signal transmission of both cytokines involved in the pathogenesis of both Psoriasis (PsO) and Psoriatic Arthritis (PsA) Objectives: Evaluate the long-term efficacy of treatment with Ustekinumab in PsA patients previously treated with TNF inhibitors (TNF-i) in real life Methods: We prospectively evaluated patients with PsO and moderate-severe PsA, who were treated with Ustekinumab after the failure of previous TNF-i therapies, in the period January 2013 -December 2015. Clinimetric scores (PASI, DAS44CRP, Pain VAS, Clinicians' VAS, and HAQ) were assessed and biochemical values (ESR, CRP, glucose, cholesterol, uric acid) were measured at baseline (T0) and after 6 (T6), 12 (T12) and 24 (T24) months. Differences between variables were analysed with paired T test (P<0.05 as significant) Results: 36 patients (61% men; age (mean±DS): 49.7±11.4) treated with ustekinumab were evaluated (Figure 1 A). In 6/36 (16.7%) patients treated with ustekinumab for <12 months (mean duration: 7.5 months), a significant reduction of PASI (P=0.02) and Pain VAS (P=0.04) was observed after 6 months of treatment. In patients treated continuously for 12 months, a significant reduction of PASI (P<0.0001), DAS44 (P=0.008), ESR (P=0.03), CRP (P=0.04), and HAQ (P=0.002) was achieved. At T24, a persistent reduction of PASI (P<0.0001), DAS44 (P=0.04), and HAQ (P=0.02) with the rspect to T0 (Figure 1 B, C, D) was maintained. Prevalence of patients on DMARDs was higher at T0 (83%) compared to the prevalence after the beginning of the ustekinumab therapy (36%). No significant differences in metabolic parameters were observed during the follow-up while a trend in reduction of uric acid resulted (2.8±2.7 at T0 vs 1±2 at T24). Conclusions: Ustekinumab offers a therapeutic benefit in PsO/PsA patiens who failed TNF-i providing good clinical response both at the skin and joint level. Disclosure of Interest: None declared